Socio-Demographic Factors Contributing to Premarital Sex Among Students of The University of Ilorin - Kamaluddeen Adekunle Uthman (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The practice of premarital sex has been increasing drastically lately. With the rate at which students of the Universities are involved in the practice of premarital sex, this study examines the socio-demographic factors contributing to premarital sex among students of the University of Ilorin. Specifically, this study examined if family background and peer influence are contributing factors to premarital sex among students of the University of Ilorin. The population comprised Undergraduate students of the University of Ilorin. Stratified and Systematic random sampling techniques were used to select 180 respondents for the study. A validated questionnaire tested for reliability through the split-half method using Cronbach Alpha which generated 76 was used for the study. Inferential statistics of chi-square (x2) were used to analyse the postulated null hypotheses. The finding revealed that family background and peer influence are contributing factors to premarital sex among students of the University of Ilorin. It is, therefore, recommended that parents should care for their wards/children, give them a listening ear and guide them in necessary steps to avoid them falling into being involved in premarital sex. Students should know the type of friends they keep.